The Recovery of the Diquis River: A Riverbank in an Indigenous Reservation (Biocenosis, 2022)
It reflects on the territorial recovery struggles of indigenous peoples of Costa Rica and how since the recovery of their lands, the waters, springs, streams and rivers have been protected, helping to clean up the waters of the Diquis River, known as Terraba river. The article shows different views of this river that has historically been accompanied by the indigenous reservation. It comments on the environmental and social problems suffered by indigenous peoples, as well as on the importance of their recent autonomous struggles in defense of their lands, forests and waters.
Keywords: water protection; Diquís river; indigenous territorial recovery; natural regeneration; indigenous autonomy